PROMOSI KESEHATAN DI KALANGAN REMAJA MELALUI MEDIA: LITERATUR REVIEW - marsiana wibowo; Erni Gustina (Universitas Respati Yogyakarta, 2020)
Background: the development of the media today is very influential in adolescent behavior in daily life. Teenagers use the media to search for information they don't know about. Media with the internet is a media that is very easily accessible and valuable for adolescents to access various health issues. Some scientific discussions see the potential of the media as a tool to promote positive health behaviors in adolescents.Objective to identify the potential of the media as a tool to promote positive health behaviors in adolescents. Methods: The methodology used is the literature literature in which we examine research that is relevant to the use of media as health promotion among adolescents. Literature is obtained from journal link searches such as pubmed, google schoolar. Publication articles used as literature have inclusion criteria such as the media used are new media both print and electronic.Results: An article search returned 20 articles. After submitting 20 articles, 10 articles met the inclusion criteria. health promotion interventions using media literacy can have a positive impact on adolescent behavior. Health promotion to increase the positive behavior of adolescents can be through social networks such as Facebook, Twitter, blogs, microblogs, discussion forums.Conclusion: use of Media Literation Education (MLE) as an alternative to comprehensive sexual health education. Through MLE it is easier to introduce topics about relationships and sexual health than traditional sexual health education programs.